Effect of L-Arginine on the Serum Level of Advanced Glycation End Products in Patients with Post Infarction Chronic Heart Failure - V. Kuryata, Olexandr; Zabida, Abdunaser A. (Journal of Nutritional Therapeutics, 2017)
Post-infarction heart failure with preserved ejection fraction (HFpEF) determines a great morbidity and mortality, and given the physiopathology implications of advanced glycation end products (AGEs) in the genesis of myocardial dysfunction. As known endothelial dysfunction is an independent predictor for cardiovascular disease. L-Arginine is the amino acid with potential to improve endothelial function which leading to prevention and treatment of cardiovascular diseases, and we think that L-Arginine may decrease the serum AGEs. We aimed to estimate the value of AGEs in post-infarction HFpEF patients, and detect the effect of L-Arginine on the serum level of AGEs in post-infarction HFpEF pts. all individuals (25) included aged 40 to 80 years, 20(80%) males and 5(20%) females were diagnosed with (HFpEF) according to ESC guidelines (2012), and their functional class according to NYHA classification for HF. 20(80%) patients of them have myocardial infarction in anamnesis. 1st group:13 patients with HFpEF and history of myocardial infarction with L-Arginine added to their standard treatment. 2nd group:7 patients with HFpEF and history of myocardial infarction with standard treatment (without L-Arginine). Comparsion group: 5 patients with HFpEF with standard treatment. We prescribed L. Arginine aspartate (Tivortin 4.2gm) intravenously once daily for 10 days for all 1st group patients. The levels of total cholesterol, triglycerides, glucose, white blood cells, erythrocyte sedimentation rate and AGEs serum level were deterimined. AGEs serum level increased markedly increased in middle-age pts with post infarction HFpEF. Inclusion of L-arginine aspartate in complex of treatment for post infarction HFpEF contributed to the significant decrease AGEs level in >60 years old patients.